2019
DOI: 10.1177/0885066619843279
|View full text |Cite
|
Sign up to set email alerts
|

Midodrine as an Adjuvant to Intravenous Vasopressor Agents in Adults With Resolving Shock: Systematic Review and Meta-Analysis

Abstract: Purpose: To evaluate the effects of midodrine in addition to intravenous vasopressor therapy on outcomes in adults recovering from shock. Materials and Methods: PubMed, Scopus, Clinicaltrials.gov, and published abstracts were searched from inception to November 2018 for studies comparing outcomes in shock after midodrine initiation versus no midodrine. Results: Three studies with 2533 patients were included. Patients in whom midodrine was added to intravenous vasopressor therapy compared to intravenous vasopre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 29 publications
(58 reference statements)
2
14
0
Order By: Relevance
“…Surprisingly, two studies showed that midodrine increases hospital and ICU LOS [ 16 , 20 ]. Based on these conflicting results, our meta-analysis was performed to solve this dilemma as new studies have been published after the last meta-analysis by Hammond et al [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, two studies showed that midodrine increases hospital and ICU LOS [ 16 , 20 ]. Based on these conflicting results, our meta-analysis was performed to solve this dilemma as new studies have been published after the last meta-analysis by Hammond et al [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Midodrine is another oral vasoconstrictor frequently administered to reduce the time to norepinephrine weaning. Midodrine has been inconsistently associated with shorter vasopressor administration and ICU length of stay [ 114 , 115 , 116 ]. The recent MIDAS (effect of midodrine versus placebo on time to vasopressor discontinuation in patients with persistent hypotension in the intensive care unit) trial reported that midodrine did not reduce time to vasopressor discontinuation in patients with persistent hypotension [ 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…This finding is in keeping with the primary outcome of MIDAS, the only appropriatelypowered, randomised study of this question, 7 as well as several other studies and meta-analyses which showed no effect of midodrine on similar outcomes. [12][13][14][15] Earlier retrospective or observational studies demonstrated that midodrine accelerated either liberation from vasopressors or discharge from the ICU. 1,6,16 These differences are likely due to heterogeneous study populations, retrospective or observational designs and differing dose regimens.…”
Section: Discussionmentioning
confidence: 99%